2020
DOI: 10.1371/journal.pone.0238574
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder perspectives on large-scale marine protected areas

Abstract: Large-scale marine protected areas (LSMPAs), MPAs greater than 100,000km 2 , have proliferated in the past decade. However, the value of LSMPAs as conservation tools is debated, in both global scientific and policy venues as well as in particular sites. To add nuance and more diverse voices to this debate, this research examines the perspectives of stakeholders directly engaged with LSMPAs. We conducted a Q Method study with forty LSMPA stakeholders at five sites, including three established LSMPAs (the Marian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Engaging stakeholders in managing a touristic area allows for establishing consensus and avoiding conflicts, advancing partnership and increasing responsibility as well as building trust to public institutions [ 49 ], creating and better use of the local human and social capital of touristic areas [ 6 , 86 , 87 ], as well as adds to increased quality of the project [ 55 , 88 ]. Stakeholders participation allows to enhance multilateral influence and interaction between all actors in a given area [ 49 , 27 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Engaging stakeholders in managing a touristic area allows for establishing consensus and avoiding conflicts, advancing partnership and increasing responsibility as well as building trust to public institutions [ 49 ], creating and better use of the local human and social capital of touristic areas [ 6 , 86 , 87 ], as well as adds to increased quality of the project [ 55 , 88 ]. Stakeholders participation allows to enhance multilateral influence and interaction between all actors in a given area [ 49 , 27 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…The territorial narratives described in this analysis demonstrate that this is not the case; offshore spaces represent active social and political seascapes with which and through which people do, in fact, interact. This finding in itself is not new; a decade of research has repeatedly demonstrated that LSMPAs are associated with strong, varied interests and connections (Artis et al, 2020;Richmond and Kotowicz, 2015;Sand, 2012). Yet, the Blue Halo case in Bermuda demonstrates that even proposed marine protected areas "call forth territories" (Chmara-Huff, 2014: p. 12), or territorial practices seeking to define and order a bounded space.…”
Section: Choosing By Waiting: Implications Of the Failed Blue Halomentioning
confidence: 99%
“…The case illustrates not only the malleability of idealized space imaginaries, but also their potential to gather coalitions and build consensus. Similar to the "win-win-win" mentality found among LSMPA enthusiasts globally (Artis et al, 2020), Blue Halo proponents and opponents both used complex territorial narratives invoking seemingly competing idealized space imaginaries, simultaneously claiming conservation, economic, and sovereignty-related benefits to legitimize their offshore territorial interests. The need to address varied values through complex territorial narratives produced coalitions between historically unlikely allies.…”
Section: Choosing By Waiting: Implications Of the Failed Blue Halomentioning
confidence: 99%
See 1 more Smart Citation
“…This study focuses on the performance in regards to the fishing pressure applied to various commercial marine species across four large scale marine protected areas (LSMPAs) in four different exclusive economic zones (EEZ) in the Pacific (Hawaii, Pitcairn, Galapagos, New Caledonia; Figure 1). While there is some controversy around the definition of LSMPAs regarding their extension and the activities allowed within them, here, LSMPAs are usually considered to refer to marine protected areas in excess of 100,000 km 2 , where the allowed activities identify the IUCN category that it belongs to [10][11][12][13]. The four LSMPAs of this study are characterized by different levels of protection, i.e., they are either classified as 100% no-take (in Northwestern Hawaii and Pitcairn) or divided into different zones with varying levels of protection (multi-use; New Caledonia, Galapagos).…”
Section: Introductionmentioning
confidence: 99%